2014
DOI: 10.1016/j.ijsu.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of digital infra–red thermal imaging as an adjunctive screening method for breast carcinoma: A pilot study

Abstract: Based on the results of this study involving 1008 subjects for screening of breast cancer, thermography turns out to be a very useful tool for screening. Because it is non-contact, pain-free, radiation free and comparatively portable it can be used in as a proactive technique for detection of breast carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 13 publications
1
20
0
3
Order By: Relevance
“…e goal of another work [24] was to compare the classification results of three different classifiers (SVM, k-NN, and Naive Bayes) and use GLCM features extracted from each thermography image; they obtained the accuracy ratio of 92.5%, which corresponded to true positive fraction of 78.6% at a false positive fraction of 0%. In another pilot study [25], digital infrared thermal imaging showed promising results and is thus well suited as a screening tool, obtaining a sensitivity of 97.6%, specificity of 99.17%, positive predictive value of 83.67%, and negative predictive value of 99.89%. Its use in combination with other laboratory and outcome assessment tools could lead to a significant improvement in the management of breast cancer.…”
Section: Comparative Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e goal of another work [24] was to compare the classification results of three different classifiers (SVM, k-NN, and Naive Bayes) and use GLCM features extracted from each thermography image; they obtained the accuracy ratio of 92.5%, which corresponded to true positive fraction of 78.6% at a false positive fraction of 0%. In another pilot study [25], digital infrared thermal imaging showed promising results and is thus well suited as a screening tool, obtaining a sensitivity of 97.6%, specificity of 99.17%, positive predictive value of 83.67%, and negative predictive value of 99.89%. Its use in combination with other laboratory and outcome assessment tools could lead to a significant improvement in the management of breast cancer.…”
Section: Comparative Discussionmentioning
confidence: 99%
“…Next, we review related papers on thermographic breast image classification [1,3,4,6,[20][21][22][23][24][25][26][27][28][29][30], which is the topic of our work. Two different kinds of neural network classifiers have been compared: a feedforward neural network and a radial basis function classifier [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim como a termografia (15) , vários outros métodos de imagens têm sido aplicados na avaliação mamária, tais como mamografia, ultrassom, ressonância nuclear magnética (RNM) e cintilografia. Contudo, cada um apresenta suas vantagens e desvantagens em relação ao outro.…”
Section: Discussionunclassified
“…No entanto, ficou inviabilizada por falta de recursos técnicos e disponibilidade de profissional com especialização na área. Assim, adotou-se a termografia como um método experimental adequado para lactantes e considerado por outros autores (15) como confortável, indolor e livre de radiações (ionizantes ou não).…”
Section: Discussionunclassified